Near-field magneto-optics of quantum dots - Zora, A.; Simserides, C.; Triberis, G. (AIP Conference Proceedings, 2007)
Encouraged by the latest experimental developments as well as by the theoretical interest on the near‐field (NF) optics of semiconductor quantum dots (QDs), we present our most recent theoretical results on the NF optical absorption and photoluminescence (PL) of single and coupled III‐V QDs subjected additionally to an external magnetic field of variable orientation and magnitude. The zero‐magnetic‐field “structural” QD symmetry can be destroyed varying the magnetic field orientation. The asymmetry induced by the magnetic field ‐except for specific orientations along symmetry axes‐ can be uncovered in the near‐field but not in the far‐field spectra. Hence, we predict that NF magnetoabsorption experiments, of realistic spatial resolution, will be in the position to bring to light the QD symmetry.